Tumor lysate particle only vaccine (TLPO) vs. Tumor lysate particle-loaded, dendritic cell vaccine (TLPLDC) to prevent recurrence in resected stage III/IV melanoma patients: Results of a phase I/IIa trial - Spencer G. Van Decar; Elizabeth L. Carpenter; Alexandra M. Adams; Robert C. Chick; Guy T. Clifton; Alex Stojadinovic; Timothy J. Vreeland; Franklin A. Valdera; Ankur Tiwari; Anne E. O'Shea; Patrick M. McCarthy; Diane F. Hale; et al. (Cancer Treatment and Research Communications)
Background: The autologous tumor lysate, particle-loaded, dendritic cell (TLPLDC) vaccine is produced from dendritic cells (DC) loaded ex vivo with autologous tumor lysate (TL). TLPLDC has been shown to decrease recurrence in resected Stage III/IV melanoma patients in a Phase IIb trial. The TL particle only (TLPO) vaccine is produced by loading of yeast cell wall particles with autologous TL and direct injection allowing for in vivo DC loading. We have compared the TLPO and TLPLDC vaccines in an embedded Phase I/IIa trial of a larger Phase IIb trial of the TLPLDC vaccine. Methods: Patients rendered clinically disease-free after surgery were randomized 2:1 to receive the TLPO or TLPLDC vaccine and followed for recurrence and death. Patients had scheduled intradermal inoculations at 0, 1, 2, 6, 12, and 18 months after enrollment. Kaplan-Meier and log-rank analysis were used to compare disease-free survival (DFS) and overall survival (OS) in an intention-to-treat (ITT) analysis. Results: Sixty-three patients were randomized, 43 TLPO and 20 TLPLDC. Patients randomized to the TLPO arm were more likely to be female (37.2% vs. 10.0 %, p = 0.026), but otherwise no significant clinicopathological differences were identified. No differences in related adverse events (AE) were found between treatment arms. At a median follow-up of 20.5 months, the DFS (60.8% vs. 58.7 %, p = 0.714) and OS (94.6% vs. 93.8 %, p = 0.966) were equivalent between the TLPO and TLPLDC groups, respectively. No statistical differences were found in subgroup analyses between vaccine types, which accounted for receipt of immunotherapy and the use of G-CSF pre-blood draw. Conclusions: In a randomized, double-blind Phase I/IIa trial, there were no differences in DFS or OS in resected Stage III/IV melanoma patients receiving adjuvant TLPO versus TLPLDC vaccines. Given manufacturing advantages, further efficacy testing of TLPO is warranted in a Phase III trial.